Population Pharmacokinetics of Intravenous Acyclovir in Oncologic Pediatric Patients - Maximova, Natalia; Nisticò, Daniela; Luci, Giacomo; Simeone, Roberto; Piscianz, Elisa; Segat, Ludovica; Barbi, Egidio; Di Paolo, Antonello (Frontiers in Pharmacology, 2022)
Background. Acyclovir represents the first-line prophylaxis and therapy for herpes virus infections. However, its pharmacokinetics in children exposes them to the risk of ineffective or toxic concentrations. The study was aimed at investigating the population pharmacokinetics (POP/PK) of intravenous (IV) acyclovir in oncologic children. Methods. Patients (age, 8.65.0 years, 73 males and 47 females) received IV acyclovir for prophylaxis (n=94) and therapy (n=26) under a therapeutic drug monitoring (i.e., minimum and maximal plasma concentrations, >0.5 and <25 mg/L, respectively). Plasma concentrations were fitted by nonlinear mixed effect modeling and a simulation of dosing regimens was performed. Findings were stratified according to an estimated glomerular filtration ratio (eGFR) threshold of 250 mL/min/1.73 m2. Results. The final 1-compartment POP/PK model showed that eGFR had a significant effect on drug clearance, while allometric body weight influenced both clearance and volume of distribution. The population clearance (14.05.5 L/h) was consistent across occasions. Simulation of standard 1-h IV infusion showed that a 10-mg/kg dose every 6 h achieved target concentrations in children with normal eGFR (i.e., ≤250 mL/min/1.73 m2). Increased eGFR values required higher doses that led to an augmented risk of toxic peak concentrations. On the contrary, simulated prolonged (i.e., 2-h and 3-h) or continuous IV infusions at lower doses increased the probability of target attainment while reducing the risk of toxicities. Conclusions. Due to the variable pharmacokinetics of acyclovir, standard dosing regimens may not be effective in some patients. Prospective trials should confirm the therapeutic advantage of prolonged and continuous IV infusions.